HOLOCENE EVOLUTION OF THE HAIFA BAY AREA, ISRAEL, AND ITS INFLUENCE ON ANCIENT TELL SETTLEMENTS - Zviely D.; Sivan D.; Ecker A.; Bakler N.; Rohrlich V.; Galili E.; Boaretto E.; Klein M.; Kit E. (My University, 2006)
The geographical evolution of Haifa Bay and Zevulun Plain, Israel, from the late Pleistocene to the Holocene, is based on detailed analysis of drilled cores. At the beginning of the Holocene the Bay area was still under terrestrial conditions. Only about 9500 to 9000 cal. yr BP, when sea level rose to about 35-30 m below present sea level (b.s.l.), did Nile-derived sand start to bypass the Carmel headland and Haifa Bay come into existence as a morphological feature. Between 8000 and 7150 cal. yr BP, when sea level was 14-10 m b.s.l., the invading sea crossed the present-day coastline. At about 6800 to 6600 cal. yr BP sea level rose to about 5 m b.s.l. and flooded the Zevulun Plain up to 2 km inland, and the River Qishon estuary up to 4 km inland. It is still unknown exactly when the sea reached its maximum penetration inland but later, about 4000 years ago, the coastline in the research area was still east of the present-day coast, up to 3 km in the Zevulun Plain and 4.8 km in the River Qishon estuary. When the coastline started to retreat westward, the reclamation was followed by intensive deposition of shallow marine sand and aeolian dunes, while to the east, different wetland conditions developed. The archaeological data indicate that during the Early Bronze Age I and Early Bronze Age II, dated to between 5600 and 4700 cal. yr BP, and even later, during the Middle Bronze Age II period, about 4600 to 3500 cal. yr BP, the coastline was still east of the present-day coast, but it never actually reached the bases of most of the tells, as has been suggested, except for Tel Akko and Tel Abu Hawam.
Keywords: ISRAEL; HAIFA BAY; HOLOCENE; PALAEOGEOGRAPHY; PALAEOCOASTLINE; SEA LEVELS; HUMAN SETTLEMENT TELLS; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен